Does a prostate cancer diagnosis affect management of pre-existing diabetes? Results from PCBaSe Sweden: a nationwide cohort study. Issue 3 (16th March 2018) - Crawley, Danielle; Garmo, Hans; Rudman, Sarah; Stattin, Pär; Zethelius, Björn; Armes, Jo; Holmberg, Lars; Adolfsson, Jan; Van Hemelrijck, Mieke
Abstract : Objectives: Both prostate cancer (PCa) and type 2 diabetes mellitus (T2DM) are increasingly prevalent conditions, which frequently coexist in men. Here, we set out to specifically examine the impact of a PCa diagnosis and its treatment on T2DM treatment. Setting: This study uses observational data from Prostate Cancer database Sweden Traject. Participants: The study was undertaken in a cohort of 16 778 men with T2DM, of whom 962 were diagnosed with PCa during mean follow-up of 2.5 years. Primary and secondary outcome measures: We investigated the association between PCa diagnosis and escalation in T2DM treatment in this cohort. A treatment escalation was defined as a new or change in anti-T2DM prescription, as recorded in the prescribed drug register (ie, change from diet to metformin or sulphonylurea or insulin). We also investigated how PCa diagnosis was associated with two treatment escalations. Multivariate Cox proportional hazards regression with age as a time scale was used while adjusting for educational level and initial T2DM treatment. Results: We found no association between PCa diagnosis and risk of a single treatment escalation (HR 0.99, 95% CI 0.87 to 1.13). However, PCa diagnosis was associated with an increased risk of receiving two consecutive T2DM treatment escalations (HR 1.75, 95% CI 1.38 to 2.22). This increase was strongest for men on gonadotropin-releasing hormone (GnRH) agonists (HR 3.08, 95% CI 2.14 to 4.40). The corresponding HR for men with PCa not on hormonal treatment was 1.40 (95% CI 1.03 to 1.92) and for men with PCa on antiandrogens 0.91 (95% CI 0.29 to 2.82). Conclusions: Men with T2DM who are diagnosed with PCa, particularly those treated with GnRH agonists, were more likely to have two consecutive escalations in T2DM treatment. This suggests a need for closer monitoring of men with both PCa and T2DM, as coexistence of PCa and its subsequent treatments could potentially worsen T2DM control.